Oxidative metabolism is associated with physiological disorders in fruits stored under multiple environmental stresses. (April 2016) - Lum, Geoffrey B.; Shelp, Barry J.; DeEll, Jennifer R.; Bozzo, Gale G.
Highlights: Controlled atmosphere storage can promote physiological disorders in fleshy fruit. Oxidative stress metabolites accumulate with low O2 and/or elevated CO2 supply. GABA accumulation is regulated by redox status and should influence fruit disorders. Reduced ascorbate and glutathione minimize the stress-inducible oxidative burst. Both GABA and antioxidant metabolism are regulated by pyridine dinucleotide ratios. Abstract: In combination with low temperature, controlled atmosphere storage and 1-methylcyclopropene (ethylene antagonist) application are used to delay senescence of many fruits and vegetables. Controlled atmosphere consists of low O2 and elevated CO2 . When sub-optimal partial pressures are used, these practices represent multiple abiotic stresses that can promote the development of physiological disorders in pome fruit, including flesh browning and cavities, although there is some evidence for genetic differences in susceptibility. In the absence of surface disorders, fruit with flesh injuries are not easily distinguished from asymptomatic fruit until these are consumed. Oxidative stress metabolites tend to accumulate ( e.g., γ-aminobutyrate) or rapidly decline ( e.g., ascorbate and glutathione) in vegetative tissues exposed to hypoxic and/or elevated CO2 environments. Moreover, these phenomena can be associated with altered energy and redox status. Biochemical investigations of Arabidopsis and tomato plants with genetically-altered levels of enzymes associated with the γ-aminobutyrate shunt and the ascorbate–glutathione pathway indicate that these metabolic processes are functionally related and critical for dampening the oxidative burst in vegetative and fruit tissues, respectively. Here, we hypothesize that γ-aminobutyrate accumulation, as well energy and antioxidant depletion are associated with the development of physiological injury in pome fruit under multiple environmental stresses. An improved understanding of this relationship could assist in maintaining the quality of stored fruit.